Impact of right and left ventricular dysfunction on long-term outcome of moderate to severe secondary mitral regurgitation patients without surgical/interventional treatment. (25th November 2020) - Hu, K; Schuckart, M; Liu, D; Schimpf, V; Hermann, F; Heitzelmann, P; Lengenfelder, B; Ertl, G; Frantz, S; Nordbeck, P
Abstract: Background: Secondary mitral regurgitation (SMR) is common in aging population and related with poor outcome. Impact of right ventricular (RV) dysfunction with or without left ventricular (LV) dysfunction in this population remains unclear. The purpose of this study was to investigate the prevalence of isolated RV dysfunction and biventricular dysfunction, and to determine their prognostic implication in moderate to severe SMR without surgical/interventional treatment. Methods: A total of 1090 consecutive moderate to severe SMR patients without surgical/interventional treatment hospitalized in our hospital center between 2009 and 2018 (aged 75±12 years, 60.4% male) were included. Transthoracic echocardiography was performed at baseline to define the cardiac morphology, function and severity of MR. Clinical and echocardiographic characteristics were analyzed. All patients completed at least 1-year clinical follow-up by reviewing the medical records or telephone interview. The primary endpoint was defined as all-cause death. Results: A total of 521 patients (47.8%) reached the primary endpoint during the follow-up period [median 23 (8–40) months]. Mean left ventricular ejection fraction (LVEF) was 44.6±16.2%, and percent of patients with LVEF <50% (LV dysfunction) was 59.3%. RV dysfunction was defined as a reduced tricuspid annular plane excursion (TAPSE<17mm) or an increased systolic pulmonary artery disease (sPAP>40mmHg). Patients were divided into 4 subgroups: 1) preserved biventricular function: n=136 (12.5%); 2) isolated LV dysfunction: n=97 (8.9%); 3) isolated RV dysfunction: n=308 (28.3%); 4) biventricular dysfunction: n=549 (50.4%). The mortality in above group was 27.2%, 36.1%, 50.0%* † and 53.7%* †, respectively (*P<0.05 vs preserved biventricular function; † P<0.05 vs. isolated LV dysfunction). Multivariable survival analysis showed that isolated LV dysfunction (adjusted HR 1.78, P=0.016), isolated RV dysfunction (HR 1.59, P=0.013), or biventricular dysfunction (HR=2.14, P<0.001) were independently associated with increased all-cause mortality, after adjustment for age, sex and other clinical covariates associated with mortality including NYHA class, atrial fibrillation, hypertension, diabetes, hyperuricemia, coronary artery diseases, chronic respiratory diseases, sleep disturbance, and kidney dysfunction. Conclusions: Right ventricular dysfunction is associated with significantly higher mortality in patients with secondary mitral regurgitation without surgical/interventional treatment as compared to patients with preserved biventricular function and isolated LV dysfunction. Future studies are warranted to observe if operative strategy could significantly improve the outcome in SMR patients complicating with right ventricular dysfunction. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): German Federal Ministry of Education and Research